1994
DOI: 10.1523/jneurosci.14-03-01358.1994
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor antagonists decrease GABA outflow from the septum and increase acetylcholine outflow from the hippocampus: a microdialysis study

Abstract: The modulation of the septohippocampal cholinergic pathway by glutamatergic or GABAergic inputs was studied by monitoring the outflow of ACh collected via a transversal microdialysis probe implanted into the hippocampus and other brain areas of freely moving rats. In one set of experiments a transversal microdialysis membrane was inserted in the dorsal hippocampus, drugs were administered intracerebroventricularly through a cannula implanted in the lateral ventricle, and ACh outflow in the dialysate was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(74 citation statements)
references
References 34 publications
3
71
0
Order By: Relevance
“…Consistent with this proposal NMDA antagonists produce excessive release of Glu 42,47,48,52 and ACh 45,46,53,54 in multiple corticolimbic regions. The excessive release of neurotransmitters and subsequent overexcitation also might underlie the ability of NMDA antagonists (eg MK801, ketamine and PCP) to increase metabolism in several corticolimbic regions.…”
Section: Molecular Psychiatrysupporting
confidence: 61%
“…Consistent with this proposal NMDA antagonists produce excessive release of Glu 42,47,48,52 and ACh 45,46,53,54 in multiple corticolimbic regions. The excessive release of neurotransmitters and subsequent overexcitation also might underlie the ability of NMDA antagonists (eg MK801, ketamine and PCP) to increase metabolism in several corticolimbic regions.…”
Section: Molecular Psychiatrysupporting
confidence: 61%
“…Mechanistically, ketamine-induced disinhibition is not limited to the glutamatergic system alone and affects other neurotransmitters as well (Giovannini et al, 1994;Yan et al, 1997). It is therefore possible for acetylcholine, dopamine, or serotonin to play a mediatory role in ASSR PLF effects.…”
Section: Discussionmentioning
confidence: 99%
“…That antagonism, in turn, may cause increased glutamate-dependent excitation in downstream cortical regions like the ACC (Farber, 2003;Newcomer et al, 1999;Krystal et al, 1994Krystal et al, , 2003Konradi and Heckers, 2003). In support of this idea, preclinical studies have revealed that NMDAR antagonism results in (1) increased frontal extracellular glutamate (Moghaddam et al, 1997;Lorrain et al, 2003;Takahata and Moghaddam, 2003) and acetylcholine levels (Giovannini et al, 1994), and (2) increased spontaneous firing rate of neurons in the frontal cortex (Moghaddam and Jackson, 2003;Homayoun et al, 2004). The resulting excessive and disorganized activity of the frontal and cingulate regions could, in turn, diminish the brain's capacity to 'make sense' of the environment.…”
Section: Discussionmentioning
confidence: 99%